Pengaruh Nasionalisme Soekarno Terhadap Ketatanegaraan dan Politik Islam di Indonesia - Ferdi Yufriadi; Donna Ramadhan Fitri; Abdullah A Afifi (Perwakilan, 2023)
This article analyses the influence of Soekarno's secular nationalism in forming the Indonesian state. Soekarno, as one of Indonesia's proclaimers of independence and its first president, had a key role in shaping the new country's national identity and political direction. This article describes how Soekarno's secular views influenced the struggle for independence and the formation of the Indonesian state and how this vision of secular nationalism was reflected in various policies and programs of his government. In his writings, Soekarno emphasized the importance of Pancasila as the basis of an inclusive state ideology and reflected the spirit of secular nationalism. Soekarno's vision of secular nationalism was also reflected in his efforts to advance social and economic equality among the Indonesians and promote national independence through industrialization and the nationalization of vital assets. However, this article also highlights the controversy and criticism that Soekarno faced regarding his approach, which tended to be authoritarian in dealing with political opposition and resistance from certain religious groups. At the end of his reign, Sukarno's secular nationalist views began to be challenged by various groups who emphasized religious identity in political discourse. Overall, this article presents a comprehensive picture of the influence of Soekarno's secular nationalism in forming the Indonesian state. Although some aspects of his political approach are controversial, the legacy of Soekarno's secular nationalism remains an important part of Indonesia's national identity. It is relevant in facing the nation's future challenges.